Réponses

2013-02-25T15:41:15+01:00

A = ( a+6 )²

A = a² + 12a + 36

 

B = ( t + 10 )²

B = t² + 20t + 100

 

C = ( 5p + 4 )²

C = 25p² + 40p + 16

 

D = ( 5x + 2)²

D = 25x² + 20x + 4

 

E = ( 4x + 7 )²

E = 16x² + 56x + 49

 

F = ( 1,5b + 3.4 )²

F = 2,25b² + 10,2b + 11,56

 

G = ( 0,7 + 2z)²

G = 0,49 + 2,8z + 4z²

 

H = ( 1, 2 + y)²

H = 1,44 + 2,4y + y²

2013-02-25T16:05:59+01:00

A = a²+12a+36

B = t² + 20t +100

C = 25p² + 40p + 16

D = 25x² +20x+4

E = 16x² +56x +49

F = 2.25b² + 10.2b + 11.56

G = 0.49 +2.8z +4z²

H  = 1.44 + 2.4y +y²